Hydrolysis of Wheat Straw Hemicellulose - Sirisansaneeyakul, Sarote; Rizzi, Manfred (Agriculture and Natural Resources, 1998)
The dilute acid hydrolysis of 1.5% H2SO4, solid ratio of 1:15, particle size 0.5-1.4 mm, and 121°C for 30 min. was found as the better alternative for wheat straw hydrolysate preparation than those of the alkaline and enzymatic treatment under the conditions in this study. From scaling up to using 250 g wheat straw as substrate, an average xylose yield of 63.7% or 11.5 g xylose/100 g wheat straw (dry basis) was obtained. Also the inhibitory acetic acid was preferably removed by vacuum evaporation during the concentration of the hydrolysate. At 93% removal of water, only 78% loss of acetic acid was obtained with the remaining concentration of acetic acid 4.8 g/l in hydrolysate concentrate.